2019
DOI: 10.14202/vetworld.2019.309-315
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral activity of Pterois volitans (red lionfish) venom in the early development of human immunodeficiency virus/acquired immunodeficiency syndrome antiretroviral alternative source

Abstract: Aim: This study aimed to investigate the antiviral activity of Pterois volitans phospholipase A2 (PV-PLA2) from Indonesia to human immunodeficiency virus (HIV). Materials and Methods: Fresh venomous fin parts of wild PV specimens were collected from Java Sea waters. Then, it washed using phosphate buffer pH 7.0 and immersed in phosphate buffer pH 7.0 0.01 m containing CaCl2 0.001 m for 24 h. The immersed fin then allowed for extraction process by sonicating for 2×8 min with 80% pulse and 20 kHz output with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Finally, it caused a greater inhibition compared to the 30m sample, which was purified as stated above, but without acidification with caprylic acid by heating at a temperature of 60 °C for 30 min, as this showed inhibition of 88.01%. A greater percentage for the inhibition of Simian retrovirus serotype-2 was observed when compared to that reported by Ramadhan (2018), which showed that there was 97% inhibition using the purification method of ammonium sulfate salting gradually at a saturation level of 80% [22]. This suggests that the 20m sample has better antiretroviral activity when compared to that of lamivudine, and also, it has capabilities that are not much different from those of standard antiretroviral drugs available on the market.…”
Section: Antiretroviral Activity Test Using Srv-2mentioning
confidence: 54%
See 1 more Smart Citation
“…Finally, it caused a greater inhibition compared to the 30m sample, which was purified as stated above, but without acidification with caprylic acid by heating at a temperature of 60 °C for 30 min, as this showed inhibition of 88.01%. A greater percentage for the inhibition of Simian retrovirus serotype-2 was observed when compared to that reported by Ramadhan (2018), which showed that there was 97% inhibition using the purification method of ammonium sulfate salting gradually at a saturation level of 80% [22]. This suggests that the 20m sample has better antiretroviral activity when compared to that of lamivudine, and also, it has capabilities that are not much different from those of standard antiretroviral drugs available on the market.…”
Section: Antiretroviral Activity Test Using Srv-2mentioning
confidence: 54%
“…To ascertain the antiretroviral activity, three tests as follows: MTT assay, RT-qPCR test, and antiretroviral activity SRV-2 test were conducted [21,22]. Meanwhile, the MTT assay aims to ascertain how toxic the sample is to the human A549 cells (lung cancer cells) that were prepared in the Dulbecco's modified Eagle's medium (DMEM), which contained 100 µg/ml streptomycin, 5% fetal bovine serum (FBS), and 1000 U/ml penicillin.…”
Section: Antiretroviral Activity Test Using Srv-2mentioning
confidence: 99%
“…According to the authors, even if this range is lower than that of spearfishing, more studies are recommended to develop the traps. Sommeng et al (2019) studied the antiviral activity of P.volitans phospholipase A2 (PLA2) from Indonesia for its effects on the human immunodeficiency virus. The authors reported that PLA2 from P.volitans showed strong inhibition on the SRV2-A549 cell lines, therefore, they suggested to evaluate their effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the study of the antiretroviral activity of the PLA2 from Pterois volitans red lionfish venom showed the significant inhibition of simian retrovirus serotype-2 (SRV2) culture in vitro. It gives a certain potential for this protein to become an anti-HIV substance [ 81 ].…”
Section: Antiviral Activity Of Animal Toxinsmentioning
confidence: 99%